2022
DOI: 10.36552/pjns.v26i1.641
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcome of Ventriculoperitoneal (VP) Shunt in Terms of Improvement and Complications

Abstract: Objective:  To analyze the outcome of ventriculoperitoneal (VP) shunts in terms of improvement and complications. Material and Methods:  This retrospective observational study is done in MTI Mardan medical complex and Prime teaching hospital from September 2017 to March 2020. The hospital record of all patients who underwent ventriculoperitoneal shunts was reviewed for improvement and complications. Patients undergoing ventriculoperitoneal shunt for normal pressure hydrocephalus were excluded from this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…16 Another meta-analysis of 11 observational studies, however, showed a statistically significant difference between the two groups, depicting results in favor of antibioticimpregnated shunts. 17 The present study aimed to ascertain the frequency of VP shunt infection in vancomycindrenched VP shunts because, despite numerous attempts to reduce them, cerebrospinal fluid (CSF) shunt infections still account for 5-15% of cases of shunt surgery morbidity. We modified our current shunt infection prevention policy to include topical vancomycin (intrashunt and perishunt) to decrease the rate of shunt infections of patients at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…16 Another meta-analysis of 11 observational studies, however, showed a statistically significant difference between the two groups, depicting results in favor of antibioticimpregnated shunts. 17 The present study aimed to ascertain the frequency of VP shunt infection in vancomycindrenched VP shunts because, despite numerous attempts to reduce them, cerebrospinal fluid (CSF) shunt infections still account for 5-15% of cases of shunt surgery morbidity. We modified our current shunt infection prevention policy to include topical vancomycin (intrashunt and perishunt) to decrease the rate of shunt infections of patients at our institution.…”
Section: Introductionmentioning
confidence: 99%